Hydrodynamic cavitation-assisted tissue ablation using a continuum robotic device with heat and mass transfer considerations - Kestek, Ezgi; Demircali, Ali Anil; Akar, Unal; Ghorbani, Morteza; Kutlu, Ozlem; Ekici, Asiye Ilin Dogan; Ekici, Sinan; Kosar, Ali; Uvet, Huseyin (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Precision and efficiency constitute the main challenges in minimally invasive surgeries. Current endoscopic robotic system limitations have been sought for innovative design and optimization strategies. Moreover, the use of flexible surgical robots in high-speed flows such as cavitation flows is a problem that needs to be solved. To address these issues, the design optimization of a tendon-driven endoscopic robot based on hydrodynamic cavitation is presented in this study. The flexible part of the robot was analyzed using the Finite Element Method (FEM), where fluid-structure interactions and material mechanical properties were considered which led to the fabrication of a prototype. Employing the shadow-graphy technique, sprays emerging from the endoscopic robot were imaged at various bending angles and fluid pressures to examine carefully flow cone angle change effects. Subsequently, the results from the experiments involving ex vivo human cervix and uterus myoma tissues were included. Thermal conditions and mass transfer rates were measured according to variations in applied pressure, bending angle enabling quantitative assessment of heat diffusion and material removal efficiency at the tissue interface. This study focuses on the continuum endoscopic robots operating at high flow rates and presents an optimal working area via a prototype. Tissue experiments demonstrated that superficial endometrial ablation increased proportionally with the bending angle of the robot in both cervix and myoma tissues, which are characterized by their dense and resilient structure. The results highlight the interconnected dynamics of cone angle, flow pressure, and tissue ablation during robot bending. In short, this study presents guidelines for future studies on the design optimization of continuum robots for high-flow rate applications.
Keywords: Tendon-driven continuum robot; Endoscopic surgery robot; Hydrodynamic cavitation; Tissue ablation; Jet flow; TECHNOLOGIES; MANIPULATOR; STIFFNESS; SPRAY; MODEL; FLOW; Thermodynamics; Engineering; Mechanics